A polycarbonate-based optical grade protective film and its preparation method and application

By preparing the PA-nanoTiO2 modified film layer on the surface of the PC film, the problems of poor UV resistance and scratch resistance of the PC film are solved, and a polycarbonate-based optical-grade protective film with high light transmission, UV resistance and high surface hardness are achieved.

CN117229552BActive Publication Date: 2025-04-25HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311190916.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-04-25
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

The existing PC film materials have poor UV resistance and scratch resistance, which cannot meet the market's diversified demand for PC-based optical films.

Method used

By preparing a PA-nanoTiO2 modified film layer on the surface of the PC film, the nanotitanium dioxide is evenly dispersed in the polyacrylate emulsion by using semi-continuous emulsion polymerization method and spin coating method to improve the material's ultraviolet resistance and surface hardness.

Benefits of technology

On the basis of maintaining the high light transmittance of PC films, the UV resistance and surface hardness of composite film materials are significantly improved, and the PC films are prone to ultraviolet aging and yellowing and insufficient surface hardness are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117229552B_ABST
    Figure CN117229552B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of material preparation, and specifically provides a polycarbonate-based optical grade protective film and a preparation method thereof. Based on polycarbonate film (PC), a polyacrylate (PA) emulsion is prepared by semi-continuous emulsion polymerization, and a dispersant polyvinyl pyrrolidone (PVP) is used to uniformly disperse nano titanium dioxide (TiO2) in the PA emulsion; a PA-nano TiO2 modified film layer is prepared on the surface of the PC film by spin coating through surface modification technology, and the modified film layer is dried by an electric hot plate. The material prepared by this process can improve the anti-ultraviolet performance and surface hardness of the composite film material on the basis of maintaining the high light transmittance of the PC film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and relates to a method for preparing a polycarbonate-based optical-grade protective film, and specifically relates to a method for preparing a polycarbonate-based optical-grade protective film with high light transmittance, UV resistance and high surface hardness. Background Art

[0002] Faced with the ever-increasing technological needs and the development of automobile digitization and networking, larger video and touch screens are needed. Since single PC optical-grade film materials are easily aged by ultraviolet light and oxygen and become yellowed, and at the same time, the surface hardness of PC films for electronic display screens is relatively low, they are easily scratched during use and cannot meet the performance requirements of protective materials for electronic display screens. Therefore, it is of great significance to prepare and develop PC films that meet performance requirements, that is, to prepare PC films with high transmittance, ultraviolet protection and high surface hardness, which are not easy to oxidize and discolor, and are wear-resistant for use in automotive and other electronic display screens. This has become an important direction for the development of high-performance polycarbonate materials.

[0003] In addition, although polyacrylate (PA) emulsion has good film-forming properties, good light transmittance, and strong adhesion on the surface of PC film, its anti-ultraviolet performance is not outstanding.

[0004] Therefore, how to provide a high-transmittance composite film system that has both anti-ultraviolet performance and enhanced surface hardness and improved wear resistance has become a technical problem that needs to be solved urgently by technical personnel in this field. Summary of the invention

[0005] In view of this, the present invention discloses a method for preparing a polycarbonate-based optical-grade protective film material, aiming to solve the problem that the existing PC film materials have poor UV resistance and scratch resistance and cannot meet the current market's diversified demands for PC-based optical films.

[0006] It should be noted that, under the premise of maintaining the original high light transmittance of PC film, the common method to solve the above technical problems is surface modification, that is, preparing a protective or functional coating on its surface to improve the comprehensive performance of the material such as UV resistance and wear resistance. The modification of polymer surface and interface is one of the main research areas of polymer material science and engineering. Applying functional coating on the polymer surface through chemical or physical modification technology is an emerging way to improve the performance of the substrate and promote the functional development of products, which has attracted much attention.

[0007] Among the modified substances, nano-TiO2 with a particle size of 10-100nm is currently a good inorganic UV absorption shielding agent. The principle of shielding ultraviolet rays is to absorb and scatter ultraviolet rays. The special quantum size effect of nano-sized particles can make the light absorption band blue-shift, and the wavelength range of ultraviolet absorption is widened. When the surface of the material is irradiated by ultraviolet rays, the electrons on the valence band absorb ultraviolet rays and are excited to the conduction band, and hole-electron pairs are generated at the same time. The hole-electron pairs recombine and convert them into heat energy, so they have the function of absorbing ultraviolet rays. In addition, the size of nano-TiO2 is much smaller than the wavelength of ultraviolet rays. Nanoparticles can scatter ultraviolet light acting on them, thereby reducing the intensity of ultraviolet rays in the irradiation direction. At the same time, titanium dioxide as a film layer can increase the surface hardness of the film and improve wear resistance.

[0008] Accordingly, the present invention prepares a PA-nano TiO2 modified film layer so that the modified system has both anti-ultraviolet performance, enhanced surface hardness and improved wear resistance. Specifically, based on polycarbonate film (PC), a polyacrylate (PA) emulsion is prepared by semi-continuous emulsion polymerization, and a dispersant polyvinyl pyrrolidone (PVP) is used to uniformly disperse nano titanium dioxide (TiO2) in the PA emulsion; a PA-nano TiO2 modified film layer is prepared on the surface of the PC film by spin coating through surface modification technology, and the modified film layer is dried by an electric hot plate. The material prepared by this process can improve the anti-ultraviolet performance and surface hardness of the composite film material on the basis of maintaining the high light transmittance of the PC film.

[0009] In order to achieve the above object, the present invention provides the following technical solutions:

[0010] A method for preparing a polycarbonate-based optical grade protective film, the method comprising the following steps:

[0011] A polyacrylate PA emulsion is prepared by a semi-continuous emulsion polymerization method, and a dispersant polyvinylpyrrolidone PVP is used to uniformly disperse nano titanium dioxide TiO2 in the PA emulsion; a PA-nano TiO2 modified film layer is prepared on the surface of a PC film by a spin coating method using a surface modification technology, and the PA-nano TiO2 modified film layer is dried by an electric hot plate to obtain the polycarbonate-based optical grade protective film.

[0012] Optionally, the polyacrylate PA emulsion is prepared by a semi-continuous emulsion polymerization method, which specifically includes the following steps:

[0013] (1) Preparation of pre-emulsion:

[0014] 30-40 g of deionized water is mixed with sodium dodecyl sulfate SDS and alkylphenol polyoxyethylene ether OP-10, and then methyl methacrylate MMA, butyl acrylate BA and acrylic acid AA are added, and stirred at room temperature to obtain a pre-emulsion;

[0015] (2) Preparation of seed emulsion:

[0016] 10-18g of deionized water, 0.5-1.0g of SDS and OP-10, and 0.25g of sodium bicarbonate NaHCO3 were stirred evenly at 80°C to form seed milk; wherein the mass ratio of SDS to OP-10 was 2:1;

[0017] (3) Preparation of aqueous polyacrylate emulsion:

[0018] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drip the initiator and 1 / 3 of the pre-emulsion into the seed emulsion. After the dripping is completed, the reaction continues for 1 hour; then, the remaining pre-emulsion and initiator are dripped into the seed emulsion, and the dripping continues for 2 hours; after the reaction is completed, cool to room temperature, and filter to obtain an aqueous polyacrylate emulsion.

[0019] It should be noted that “dropping 1 / 3 of the initiator and pre-emulsion into the seed emulsion” means preparing the pre-emulsion and the initiator in two beakers respectively, using two funnels to weigh 1 / 3 of the volume respectively and slowly dropping them into the seed emulsion respectively.

[0020] Optionally, the mass of MMA is 15-23 g, the mass ratio of MMA to BA is 1:1-1:2, and the mass ratio of MMA to AA is 1:10; the mass of SDS is 0.5-1 g, and the mass ratio of SDS to OP-10 is 2:1.

[0021] Optionally, the reaction temperature in step (3) is 80° C. and the droplet acceleration rate is 0.5 ml / min.

[0022] Furthermore, the dripping rate of both times was 0.5 ml / min; the first dripping was to drip 1 / 3 of the material for 1 hour, and after the first dripping was completed, the reaction was carried out at 80°C for 1 hour, that is, the first stage lasted for 2 hours; the second dripping was to drip the remaining 2 / 3 of the material for 2 hours, and after the addition was completed, the reaction was carried out at 80°C for 2 hours, that is, the second stage lasted for 4 hours.

[0023] Optionally, the specific operation of preparing the PA-nano-TiO2 modified film layer on the surface of the PC film by spin coating through surface modification technology is as follows:

[0024] The nano-TiO2 is uniformly and stably dispersed in the pH-adjusted PA emulsion using polyvinyl pyrrolidone solution to obtain a composite emulsion; the composite emulsion is spin-coated on the pretreated PC film surface using a spin coater, and then dried to obtain the PA-nano-TiO2 modified film.

[0025] Further, the pH value of the PA emulsion is adjusted to 8-9 with ammonia water, and the addition amount of the nano-TiO2 is 0.01%-0.3% of the mass of the PA emulsion monomer, and the surface pretreatment operation of the PC film is as follows:

[0026] A PC film with a relatively uniform thickness of 5 cm×5 cm was cut out; the cut PC film was ultrasonically cleaned, then alternately cleaned with deionized water and ethanol, and dried.

[0027] Furthermore, the spin coating process parameters of the spin coater are as follows:

[0028] The spin coating speed was 800 rpm; the acceleration was 100 rpm / s; and the spin coating time was 10 s.

[0029] The present invention also seeks to protect a polycarbonate-based optical-grade protective film prepared by the above method, wherein the material of the polycarbonate-based optical-grade protective film is a PA-TiO2 / PC composite film.

[0030] Furthermore, the present invention seeks to protect the use of the polycarbonate-based optical-grade protective film prepared by the above method in an electronic display screen.

[0031] It can be seen from the above technical solutions that, compared with the prior art, the polycarbonate-based optical-grade protective film material and the preparation method and application thereof provided by the present invention have the following excellent effects:

[0032] 1) The present invention solves the incompatibility of organic and inorganic systems by selecting polyvinyl pyrrolidone with excellent compatibility, so that nano titanium dioxide is evenly and stably dispersed in organic polyacrylate, thereby improving the light transmittance, UV resistance, ductility and surface hardness of the film layer, and solving the problem that the PC film itself is prone to UV aging and yellowing;

[0033] 2) The PA-TiO2 / PC composite film prepared by the present invention can maintain the high light transmittance of the PC film and improve the light transmittance to meet the application requirements of high light transmittance.

[0034] 3) The present invention utilizes polyvinyl pyrrolidone and water-soluble polyacrylate system with excellent compatibility, which is green, environmentally friendly, non-toxic, low in cost, and conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0036] Figure 1The present invention is a flow chart of the preparation process of the polycarbonate-based optical grade protective film.

[0037] Figure 2 This is the infrared spectrum of PA emulsion.

[0038] Figure 3 Particle size distribution diagram of PA emulsion (a) and PA-TiO2 composite emulsion (b).

[0039] Figure 4 This is a comparison chart of the transmittance of PC, PA / PC, and PA-0.1%TiO2 / PC films.

[0040] Figure 5 Comparison of the transmittance of PC and PA-TiO2 / PC films after aging for 24h (a), 48h (b), and 120h (c).

[0041] Figure 6 Yellowness index YI graph of PC and PA-TiO2 / PC films after aging for 0, 24, 48, and 120 hours.

[0042] Figure 7 This is a comparison chart of the elongation at break of PC, PA / PC, and PA-TiO2 / PC before and after aging.

[0043] Figure 8 These are the stress-strain curves of PC, PA / PC, and PA-TiO2 / PC after aging.

[0044] Fig. 9 This is the PA-TiO2 / PC surface hardness test chart. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The embodiment of the invention discloses a method for preparing a polycarbonate-based optical-grade protective film material.

[0047] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0048] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0049] Example 1

[0050] A method for preparing a polycarbonate-based optical grade protective film comprises the following steps:

[0051] 1. Pretreatment of PC film:

[0052] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0053] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0054] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0055] Second, it plays the role of activating the base bed on the surface of the PC film;

[0056] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0057] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0058] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0059] 2. Preparation of polyacrylate emulsion

[0060] 30 g of deionized water, 0.5 g of sodium dodecyl sulfate SDS, and 0.25 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 23 g of methyl methacrylate MMA, 30 g of butyl acrylate BA, and 2.3 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0061] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.36 g of SDS, 0.18 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0062] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0063] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0064] 3. Preparation of PA-TiO2 / PC composite film

[0065] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.01% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine for drying, and after drying, it was stored away from light and oxygen.

[0066] Example 2

[0067] 1. Pretreatment of PC film:

[0068] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0069] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0070] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0071] Second, it plays the role of activating the base bed on the surface of the PC film;

[0072] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0073] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0074] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0075] 2. Preparation of polyacrylate emulsion

[0076] 40 g of deionized water, 0.65 g of sodium dodecyl sulfate SDS, and 0.325 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 15 g of methyl methacrylate MMA, 36 g of butyl acrylate BA, and 1.5 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0077] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.38 g of SDS, 0.16 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed emulsion.

[0078] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0079] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0080] 3. Preparation of PA-TiO2 / PC composite film

[0081] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.05% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine to dry, and after drying, it was stored away from light and oxygen.

[0082] Example 3

[0083] 1. Pretreatment of PC film:

[0084] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0085] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0086] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0087] Second, it plays the role of activating the base bed on the surface of the PC film;

[0088] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0089] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0090] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0091] 2. Preparation of polyacrylate emulsion

[0092] 40 g of deionized water, 0.72 g of sodium dodecyl sulfate SDS, and 0.36 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 20 g of methyl methacrylate MMA, 30 g of butyl acrylate BA, and 2 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0093] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.48 g of SDS, 0.24 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0094] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0095] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0096] 3. Preparation of PA-TiO2 / PC composite film

[0097] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.1% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine for drying, and after drying, it was stored away from light and oxygen.

[0098] Example 4

[0099] 1. Pretreatment of PC film:

[0100] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0101] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0102] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0103] Second, it plays the role of activating the base bed on the surface of the PC film;

[0104] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0105] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0106] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0107] 2. Preparation of polyacrylate emulsion

[0108] 40 g of deionized water, 0.36 g of sodium dodecyl sulfate SDS, and 0.18 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 18 g of methyl methacrylate MMA, 36 g of butyl acrylate BA, and 1.8 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0109] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.5 g of SDS, 0.25 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0110] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0111] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0112] 3. Preparation of PA-TiO2 / PC composite film

[0113] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.15% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine for drying, and after drying, it was stored away from light and oxygen.

[0114] Example 5

[0115] 1. Pretreatment of PC film:

[0116] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0117] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0118] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0119] Second, it plays the role of activating the base bed on the surface of the PC film;

[0120] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0121] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0122] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0123] 2. Preparation of polyacrylate emulsion

[0124] 40 g of deionized water, 0.8 g of sodium dodecyl sulfate SDS, and 0.4 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 23 g of methyl methacrylate MMA, 30 g of butyl acrylate BA, and 2.3 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0125] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.48 g of SDS, 0.24 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0126] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0127] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0128] 3. Preparation of PA-TiO2 / PC composite film

[0129] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.18% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine for drying, and after drying, it was stored away from light and oxygen.

[0130] Example 7

[0131] 1. Pretreatment of PC film:

[0132] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0133] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0134] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0135] Second, it plays the role of activating the base bed on the surface of the PC film;

[0136] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0137] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0138] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0139] 2. Preparation of polyacrylate emulsion

[0140] 40 g of deionized water, 0.36 g of sodium dodecyl sulfate SDS, and 0.18 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 18 g of methyl methacrylate MMA, 30 g of butyl acrylate BA, and 1.8 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0141] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.5 g of SDS, 0.25 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0142] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0143] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0144] 3. Preparation of PA-TiO2 / PC composite film

[0145] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.20% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine to dry, and after drying, it was stored away from light and oxygen.

[0146] Example 8

[0147] 1. Pretreatment of PC film:

[0148] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0149] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0150] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0151] Second, it plays the role of activating the base bed on the surface of the PC film;

[0152] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0153] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0154] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0155] 2. Preparation of polyacrylate emulsion

[0156] 40 g of deionized water, 0.36 g of sodium dodecyl sulfate SDS, and 0.18 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 18 g of methyl methacrylate MMA, 20 g of butyl acrylate BA, and 1.8 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0157] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.5 g of SDS, 0.25 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0158] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0159] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0160] 3. Preparation of PA-TiO2 / PC composite film

[0161] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.23% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine for drying, and after drying, it was stored away from light and oxygen.

[0162] Example 9

[0163] 1. Pretreatment of PC film:

[0164] Slicing: Use a paper cutter to cut out 5cm×5cm PC films with relatively uniform thickness. The thickness of each group of films should be within 2μm.

[0165] Ultrasonic cleaning: The cut PC samples are ultrasonically cleaned for the following purposes:

[0166] One is to clean the surface of the PC film to remove dirt and particles on the surface;

[0167] Second, it plays the role of activating the base bed on the surface of the PC film;

[0168] The principle is to remove the oxide on the surface of the PC film through the mechanical vibration of ultrasound and the force of the fluid to activate its surface base bed.

[0169] Cleaning: First rinse with deionized water to remove impurities and dirt on the surface, then rinse with ethanol to remove organic dirt on the surface, and finally rinse with deionized water to remove residual ethanol and other impurities.

[0170] Drying: Place the treated PC films in groups and place them in an oven for drying.

[0171] 2. Preparation of polyacrylate emulsion

[0172] 40 g of deionized water, 0.36 g of sodium dodecyl sulfate SDS, and 0.18 g of alkylphenol polyoxyethylene ether OP-10 were mixed in a beaker, and then 18 g of methyl methacrylate MMA, 19 g of butyl acrylate BA, and 1.8 g of acrylic acid AA were added, and the mixture was stirred thoroughly at room temperature to obtain a uniform pre-emulsion.

[0173] The prepared pre-emulsion was placed on a magnetic stirrer to maintain uniformity; then 15 g of deionized water, 0.5 g of SDS, 0.25 g of OP-10, and 0.25 g of sodium bicarbonate NaHCO3 were stirred evenly in a three-necked flask at room temperature, and the system was stirred and heated to 80°C using a heat-collecting constant temperature heating magnetic stirrer to form a seed milk.

[0174] Use 25g of deionized water to dissolve 0.3g of potassium persulfate KPS to obtain an initiator solution, and drop the initiator and 1 / 3 of the pre-emulsion into the seed latex for 1 hour. After the dropwise addition is completed, the reaction continues for 1 hour. After the reaction is completed, the remaining pre-emulsion and initiator are added dropwise to the seed latex, and the dropwise addition continues for 2 hours.

[0175] The polymerization reaction was continued at 80°C for 2 hours. After the reaction, the sample was cooled to room temperature. The aqueous polyacrylate emulsion was filtered through a 200-mesh sieve to obtain the aqueous polyacrylate emulsion. Finally, the aqueous polyacrylate emulsion was transferred to a beaker, and the pH value of the emulsion was adjusted to 8-9 with ammonia NH3·H2O. After the adjustment was completed, the final pH value was recorded.

[0176] 3. Preparation of PA-TiO2 / PC composite film

[0177] Polyvinyl pyrrolidone (PVP) solution was used to uniformly and stably disperse 0.3% titanium dioxide TiO2 by mass of PA emulsion monomer in PA emulsion with adjusted pH to obtain a composite emulsion; the composite emulsion was spin-coated on the pretreated PC film surface using a spin coater, and the experimental parameters were optimized to select the film preparation parameters: speed 800 rpm; acceleration 100 rpm / s; time 10 s; after the end, the sample was taken out and placed on a glue baking machine to dry, and after drying, it was stored away from light and oxygen.

[0178] Next, in order to further highlight the excellent effect of the technology of the present invention, the inventors also conducted the following comparative experiments and performance measurements, as follows:

[0179] Experiment 1: used to illustrate the successful synthesis of PA emulsion

[0180] Take 0.5 ml of PA emulsion sample and put it into a sample tube, and apply the liquid sample thinly on the surface of potassium bromide tablet; use Fourier transform infrared spectrometer to test the PA emulsion by infrared spectrum, and use the infrared spectrum to evaluate whether the PA emulsion is successfully synthesized. Figure 2 As shown in the figure, 3443.06cm -1 The broad peak at 2957 cm-1 corresponds to the OH stretching vibration. -1 and 2874.06cm -1 The absorption peak at 1731.18 cm -1 The peak at 1386-1457 cm -1 The peaks at 1274.63 and 1133.14 cm correspond to the CH bending vibrations in the methyl group. -1 The peak at belongs to the CO symmetric stretching vibration, which is the characteristic absorption peak of acrylic polymers. The successful polymerization of PA can be analyzed by infrared characteristic peaks.

[0181] After the PA emulsion is prepared, the monomer conversion rate is calculated according to the following steps, and the degree of monomer polymerization is evaluated by the degree of monomer conversion into polymer.

[0182] Take a dry and clean surface dish and weigh its mass, then spread a small amount (about 1.5-2g) of the composite emulsion on it, and finally put it into a constant temperature blast drying oven at 80℃ to dry to constant weight. The monomer conversion rate C is calculated according to formula (1):

[0183]

[0184] Wherein, C is the monomer conversion rate (%), M0 is the mass of the watch glass, M1 is the mass of the emulsion sample and the watch glass, M2 is the total mass of the sample and the watch glass after drying to constant weight, M3 is the total mass of the raw materials in the formula, M4 is the total mass of the non-volatile substances in the formula, and M5 is the total mass of the acrylate monomer.

[0185] The emulsion monomer conversion rate C measured experimentally is 91.50%, which indicates that the polymerization process has been relatively sufficient and the synthesis of polyacrylate is relatively successful.

[0186] Experiment 2: used to illustrate that nano-TiO2 is uniformly and stably dispersed in PA emulsion

[0187] PA emulsion and PA-TiO2 composite emulsion were diluted with deionized water to a suitable concentration, and 3 ml of the diluted liquid was added to a cuvette; the particle size of PA emulsion and PA-TiO2 composite emulsion was tested by laser particle size analyzer, and the dispersion index (PDI) of the two emulsions was 0.053 and 0.029, respectively. Both values ​​were low, indicating that the particle size distribution of the particles in the emulsion was very narrow and the particle size was relatively uniform. This uniform particle size distribution helps the dispersion of particles during the coating process, making the coating more uniform and the surface quality of the film layer higher.

[0188] Depend on Figure 3 As shown, the average particle size (AVE) of PA emulsion is 93.87nm, while the AVE of PA-TiO2 composite emulsion is only 105nm, indicating that titanium dioxide is evenly and stably dispersed in PA emulsion without agglomeration, which means that the particle size in the emulsion is small and the coating formed is uniform and compact.

[0189] Experiment 3: Used to illustrate the high light transmittance of PA-TiO2 / PC composite film

[0190] The transmittance of PC and PA-TiO2 / PC films was tested using a UV-Vis-NIR spectrophotometer. By comparing the transmittance tests of PC and PA-TiO2 / PC films, it was found that the transmittance of the modified film with composite nano-TiO2 can reach 90%, which is higher than the transmittance of the pure PC film before modification. A film with a transmittance higher than 90% is considered to be a high-transmittance film, which is suitable for the application requirements of optical protective films.

[0191] Figure 4 It is the transmittance of PC, PA / PC, and PA-0.1%TiO2 / PC samples in the ultraviolet-near infrared-visible light region measured by a UV-visible-near infrared spectrophotometer. Figure 4 It can be seen that after the PA and PA-TiO2 coatings are applied on the surface of the PC film with high transmittance, the transmittance of the sample in the UV-visible region is still very high, and is slightly higher than PC at most wavelengths; and after modification, it is still greater than 90%, which is a high transmittance. The main reason for the above phenomenon is that PA can reduce the roughness of the PC film surface and reduce the scattering of light.

[0192] Experiment 4: Used to illustrate the anti-ultraviolet performance of PA-TiO2 / PC composite film

[0193] UV aging test

[0194] The UV aging box was used to conduct artificial accelerated aging tests to verify the UV resistance of the composite film; PA-TiO2 / PC composite film and pure PC film were taken respectively, and 5 parallel samples were prepared for each group of samples. Four gradient times were used to prepare 20 PA-TiO2 / PC composite films and 20 pure PC films; the wavelength of the fluorescent UV lamp in the UV aging box used in the experiment was 280-315nm, the lamp power was 40W, and the lamp length was 1220mm. UV aging temperature: 50 degrees Celsius; aging time: 24, 48, 120h.

[0195] Transmittance comparison before and after aging

[0196] from Figure 5 Before medium aging, the transmittance of the modified composite film is greater than that of the pure PC film and can reach 95%; after aging, the transmittance of the modified composite film is still greater than that of the pure PC film and exceeds 90%, which still belongs to the category of high transmittance film.

[0197] Comparison of yellow index before and after aging

[0198] Depend on Figure 6 It can be seen that the yellowness index of the sample increases with the aging time. The larger the yellowness index, the higher the yellowing degree of the material. Comparing the yellowness index of PC and PA-TiO2 / PC samples at different UV aging times, it can be seen that with the increase of aging time, the yellowness index of pure PC film increases more than that of modified PA-TiO2 / PC composite film, that is, the anti-ultraviolet performance of pure PC is not as good as that of modified PA-TiO2 / PC composite film.

[0199] Comparison of mechanical properties before and after aging

[0200] like Figure 7 It can be seen that the UV aging process has a certain impact on the mechanical properties of the film, but the modified film still shows good ductility after aging. Figure 8 It can be seen that the yield point decreases, which means that the film enters the plastic deformation stage when subjected to a small external force, and the flexibility of the modified film is improved; while the ultimate strength does not change much, indicating that the tensile strength of the modified film remains basically unchanged. From the perspective of optical performance comparison, the PC film has been greatly improved in terms of anti-ultraviolet aging discoloration and yellowing after modification, and the composite film has stronger anti-ultraviolet performance; and the elongation at break after aging is still higher than that of the PC film, which also proves that the composite film has anti-ultraviolet performance.

[0201] Experiment 5: Used to illustrate the wear resistance of PA-TiO2 / PC composite film

[0202] The abrasion resistance of the coating is evaluated by the pencil hardness test. Use pencils of different hardness to scratch the coating, starting from the softest pencil and gradually increasing the hardness, and observe the scratches on the coating surface. Record the hardness of the first pencil that leaves a visible scratch as the hardness of the coating. Fig. 9 As shown, the hardness of the modified film surface is increased from H before modification to 2H through the pencil hardness test.

[0203] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a polycarbonate-based optical grade protective film, characterized in that: The method comprises the following steps: A polyacrylate PA emulsion is prepared by a semi-continuous emulsion polymerization method, and a dispersant polyvinyl pyrrolidone PVP is used to uniformly disperse nano titanium dioxide TiO2 in the PA emulsion; a PA-nano TiO2 modified film layer is prepared on the surface of a PC film by a spin coating method through a surface modification technology, and the PA-nano TiO2 modified film layer is dried by an electric hot plate to obtain the polycarbonate-based optical grade protective film; The polyacrylate PA emulsion is prepared by a semi-continuous emulsion polymerization method, which specifically includes the following steps: (1) Preparation of pre-emulsion: Deionized water, sodium dodecyl sulfate SDS, and alkylphenol polyoxyethylene ether OP-10 are mixed, and then monomers methyl methacrylate MMA, butyl acrylate BA, and acrylic acid AA are added, and stirred and mixed at room temperature to obtain a pre-emulsion; (2) Preparation of seed milk: Deionized water, sodium dodecyl sulfate SDS, alkylphenol polyoxyethylene ether OP-10, and sodium bicarbonate NaHCO3 were stirred uniformly at 80°C to form seed milk; (3) Preparation of water-based polyacrylate emulsion: Dissolve 0.3 g of potassium persulfate KPS in 25 g of deionized water to obtain an initiator solution, drip the initiator and 1 / 3 of the pre-emulsion into the seed emulsion, and continue the reaction for 1 hour after the dripping is completed; then drip the remaining pre-emulsion and initiator into the seed emulsion, and continue the dripping for 2 hours; after the reaction is completed, cool to room temperature, and filter to obtain an aqueous polyacrylate emulsion; In step (1), the mass ratio of sodium dodecyl sulfate SDS to alkylphenol polyoxyethylene ether OP-10 is 2:1, the mass ratio of methyl methacrylate MMA to butyl acrylate BA is 1:1-1:2, and the mass ratio of methyl methacrylate MMA to acrylic acid AA is 1:10; The added amount of the nano titanium dioxide TiO2 is 0.01% to 0.3% of the mass of the polyacrylate PA emulsion monomer.

2. The method for preparing a polycarbonate-based optical grade protective film according to claim 1, characterized in that: In step (2), the mass ratio of sodium dodecyl sulfate SDS to alkylphenol polyoxyethylene ether OP-10 is 2:

1.

3. The method for preparing a polycarbonate-based optical grade protective film according to claim 1, characterized in that: The reaction temperature in step (3) is 80°C and the droplet acceleration rate is 0.5 ml / min.

4. The method for preparing a polycarbonate-based optical grade protective film according to claim 1, characterized in that: The specific operation of preparing the PA-nano-TiO2 modified film layer on the surface of the PC film by spin coating through surface modification technology is as follows: The nano-titanium dioxide TiO2 is uniformly and stably dispersed in the polyacrylate PA emulsion with adjusted pH by using polyvinyl pyrrolidone solution to obtain a composite emulsion; the composite emulsion is spin-coated on the pretreated PC film surface by a spin coater, and then dried to obtain the PA-nano-TiO2 modified film.

5. The method for preparing a polycarbonate-based optical grade protective film according to claim 4, characterized in that: The surface pretreatment of PC film is as follows: A PC film with a relatively uniform thickness of 5 cm×5 cm was cut out; the cut PC film was ultrasonically cleaned, then alternately cleaned with deionized water and ethanol, and dried.

6. The method for preparing a polycarbonate-based optical grade protective film according to claim 4, characterized in that: The spin coating process parameters of the spin coater are as follows: The spin coating speed was 800 rpm; the acceleration was 100 rpm / s; and the spin coating time was 10 s.

7. A polycarbonate-based optical grade protective film prepared by the method of claim 1, characterized in that: The material of the polycarbonate-based optical-grade protective film is a PA-TiO2 / PC composite film.

8. Use of the polycarbonate-based optical-grade protective film prepared by the method of claim 1 or the polycarbonate-based optical-grade protective film of claim 7 in an electronic display screen.

Citation Information

Patent Citations

  • Long-acting antifog antifrost film, and preparation method thereof

    CN109180983A

  • Core-shell structure polyacrylate emulsion and preparation method thereof

    CN115433321A